2021
DOI: 10.1016/j.xphs.2020.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Hepatocyte Spheroid Model as a 3D In Vitro Platform for Metabolism Studies

Abstract: 3D cultures of primary human hepatocytes (PHH) are emerging as a more in vivo-like culture system than previously available hepatic models. This work describes the characterisation of drug metabolism in 3D PHH spheroids. Spheroids were formed from three different donors of PHH and the expression and activities of important cytochrome P450 enzymes (CYP1A2, 2B6, 2C9, 2D6, and 3A4) were maintained for up to 21 days after seeding. The activity of CYP2B6 and 3A4 decreased, while the activity of CYP2C9 and 2D6 incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 55 publications
(66 reference statements)
3
46
0
Order By: Relevance
“…Similarly, another recent study by Kanebratt et al (2021) applying empirical scaling factors. Furthermore, the study by Kanebratt et al (2021) indicated a trend towards more pronounced deviation between predicted and observed clearance data for drug compounds with higher clearance, which was not evident in our study. Interestingly, the authors pooled three spheroids per incubation in order to increase the metabolic capacity and observed comparable CL int data using pooled and individual hepatocyte spheroids.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, another recent study by Kanebratt et al (2021) applying empirical scaling factors. Furthermore, the study by Kanebratt et al (2021) indicated a trend towards more pronounced deviation between predicted and observed clearance data for drug compounds with higher clearance, which was not evident in our study. Interestingly, the authors pooled three spheroids per incubation in order to increase the metabolic capacity and observed comparable CL int data using pooled and individual hepatocyte spheroids.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, cellular polarization was clearly present in pHH spheroids as shown by MRP2 [ 51 , 53 ], P-glycoprotein (Pgp), [ 54 ], and BSEP expression [ 53 , 54 ]. Drug-metabolizing enzyme expression and activity of CYP1A2 [ 53 , 55 , 56 , 57 ], CYP2B6 [ 55 ], CYP2C9 [ 55 ], CYP2C19 [ 58 ], CYP2D6 [ 53 , 55 , 57 ], CYP3A4 [ 50 , 53 , 55 , 56 , 57 , 58 , 59 ], and UGTs [ 56 , 59 ] was stable over several weeks of pHH spheroid culture. CYP2C9 activity even increased with culture time [ 53 , 55 , 56 , 58 ], while CYP2C8 [ 53 , 56 ], and in some cases also CYP1A2, CYP2B6, CYP2D6 and CYP3A4 [ 55 , 58 ] activities decreased with time.…”
Section: Three-dimensional Culture Models For Human Hepatocytesmentioning
confidence: 99%
“…18 In a 3D cell configuration, hepatocytes are inclined to interact in a three-dimensional space, improving their polarity and preventing PHHs dedifferentiation; hence, this environment more closely resembles the in vivo hepatocyte architecture. 61,62 Fueled by the possibility to develop hepatic culture methods characterised by prolonged maintenance of the metabolic phenotype, intense efforts have been made to deeply characterise 3D hepatocyte spheroids. They are generated with two main techniques: Formation of tubular-structure after 20 days in culture; expression of GM130 and secretin receptor (cell polarisation); primary cilia extended in the lumen [81] Cholangiocytes derived from hiPSC Expression of biliary markers (eg CK7, CK19); primary cilia; MDR1 functional activity assessed by the use of rhodamine 123; functional secretory cholangiocytes activity assessed by the exposure to somatostatin and secretin [83] Cholangiocytes derived from hiPSC Expression of biliary markers (eg CK7, CK19); MDR1 functional activity assessed by the use of rhodamine 123; CFTR functional activity assessed by the use of forskolin (i) by self-aggregation, plating a well-defined cell number in an ultralow attachment (ULA) plate, generating size-controlled spheroids, and (ii) by embedding hepatocytes in a hydrogel mimicking ECM protein (Matrigel™ or type I collagen).…”
Section: Three-dimensional Hepatocytes Spheroid: Methods Characteristics and Future Perspectivesmentioning
confidence: 99%
“…In standard 2D cultures, hepatocyte polarity is not retained and its loss is implicated as one of the main causes related to the dedifferentiation process 18 . In a 3D cell configuration, hepatocytes are inclined to interact in a three‐dimensional space, improving their polarity and preventing PHHs dedifferentiation; hence, this environment more closely resembles the in vivo hepatocyte architecture 61,62 …”
Section: Three‐dimensional Culture Models: a Novel Tool For In Vitro Liver Studiesmentioning
confidence: 99%
See 1 more Smart Citation